Defining Active Learning: A Restricted Systematic Review - Doolittle, Peter; Wojdak, Krista; Walters, Amanda (Teaching and Learning Inquiry, 2023)
What is active learning? While active learning has been demonstrated to have positive impacts on student learning and performance, defining the concept has been elusive. Previous research examining active learning definitions in STEM fields found that the vast majority of published articles did not define active learning, and those that did defined active learning as interacting, engaging, or not lecturing. The current research extends this STEM-focused work by examining both social science and STEM science publications. A restricted systematic review of literature was conducted using the SCOPUS database, resulting in 547 relevant articles focused on active learning from 2017 to 2022. An examination of the articles indicated that 71% of the reviewed articles did not define active learning and that the instructional strategies most often cited as fostering active learning emphasized social interactive learning strategies (e.g., small groups, team-based learning, discussion, and cooperative learning), as well as critical thinking strategies (e.g., problem-based learning, case-based learning, and inquiry-based learning). In addition, an in-depth qualitative analysis of the 161 definitions provided within the articles yielded three main emergent themes: (a) active learning is defined as grounded in student-centered constructivist theory, (b) active learning is defined as promoting higher-order thinking and deep learning, and (c) active learning is defined as an instructional strategy involving activity, participation, and engagement. Given these main findings, a representative definition was created: Active learning is a student-centered approach to the construction of knowledge focused on activities and strategies that foster higher-order thinking. Click here to read the corresponding ISSOTL blog post.